West Nile Virus in New York City - Lopez, Wilfredo (American Public Health Association, 2002)
In 1999, a cluster of encephalitis cases was detected in New York City. The city applied larvicide to standing water and aerially sprayed pesticides to control adult mosquitoes. The causative agent was West Nile virus, a type of encephalitis that had never before been transmitted in the western hemisphere. This experience offers many lessons for the practitioners of public health and of public health law. A public health infrastructure that does not lose sight of the old threats must be maintained. The public health and environmental governmental establishments must work together. Law is closely intertwined with policy and programmatic initiatives and can facilitate a better public health outcome.